Meningkatkan Kemampuan Konsentrasi Anak Melalui Kegiatan Menuang Air Sirup Ke Dalam Botol - Retno Ningdyah; Herman Herman; Ainun Marhamah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study aims to obtain data on the results of learning the concentration of children in group B in TK Kartika 751 Sentani Jayapura before taking action, taking action, and after taking action through pouring syrup water into bottles as an effort to improve the concentration ability of children in group B in TK Kartika VI-10 Yonif 751/R Sentani Jayapura. In this case, the child's concentration ability is lacking because the activities provided are less attractive, and the media used does not optimize the function of the five senses. The type of this research is Classroom Action Research, with the research subject being group B TK Kartika 751/R Sentani Jayapura, totaling eight children. This research uses Problem Based Learning method. The data obtained show that pouring syrup water into a bottle can increase the ability of children's concentrate.